1988
DOI: 10.1161/01.str.19.2.217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CDP-choline on neurologic deficits and cerebral glucose metabolism in a rat model of cerebral ischemia.

Abstract: The effects of cytidine 5'-diphosphocholine (CDP-choline) on neurologic deficits and cerebral glucose metabolism were studied in a rat model of transient cerebral ischemia. Cerebral ischemia was induced by occluding both common carotid arteries for 20 or 30 minutes 24 hours after the vertebral arteries were permanently occluded by electrocautery. CDP-choline was administered intraperitonealry twice daily for 4 days after reestablishing carotid blood flow. CDP-choline at two dosages (50 and 250 mg/kg) shortened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0
3

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 27 publications
0
39
0
3
Order By: Relevance
“…The relevance of this mechanism was challenged, however, because acetylcholine concentrations were not significantly increased by citicoline treatment. 130 In addition, citicoline was shown to reduce oxidative stress.…”
Section: Citicolinementioning
confidence: 99%
“…The relevance of this mechanism was challenged, however, because acetylcholine concentrations were not significantly increased by citicoline treatment. 130 In addition, citicoline was shown to reduce oxidative stress.…”
Section: Citicolinementioning
confidence: 99%
“…3 In models of transient global ischemia, CIT reduced production of free fatty acids, a tissue-toxic byproduct of membrane breakdown secondary to an ischemic insult. 3 Additionally, CIT improved neurological outcome 4 and increased survival time in global chronic hypoxia. 5 In models of temporary focal ischemia, CIT reduced the size of cerebral infarcts 6,7 and extended the duration of ischemia required to produce a given behavioral deficit or infarct size.…”
mentioning
confidence: 97%
“…Regarding neurological function, however, data are uncertain. Several studies assessing global (Kakihana et al 1988) and focal (Aronowski et al 1996;Hurtado et al 2007) cerebral ischemia models have reported an improvement on neurological outcome, while other studies could not found differences after citicoline treatment (Schabitz et al 1996(Schabitz et al , 1999. However, no systematic review has explored the adherence of citicoline experimental research on stroke models to the Stroke Therapy Academic Industry Roundtable (STAIR) recommendations (STAIR 1999).…”
mentioning
confidence: 99%